SISTEM PERINGATAN DINI KEBAKARAN HUTAN MENGGUNAKAN MODUL NODEMCU DAN BOT TELEGRAM DENGAN KONSEP INTERNET OF THINGS (IOT) - Mohamad Jamil; Hafid Saefudin; Sarby Marasabessy (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Forests have an important role in the life of living things. Nowadays forest fires (Karhutla) become a serious problem that can disrupt the symbiosis and life chain of living things. This problem has become a concern for the community, government and the world. Data obtained until August 2019 recorded 328,724 hectares and burned forest land. To overcome this problem, the government has made various efforts in the form of appeals or legal sanctions on actions that threaten forest sustainability whether carried out individually or in groups. Many cases of forest fires are known when a fire has occurred and little can be detected early. Information on the occurrence of many fires was obtained by residents around the location of the fire. To get the help of the fire department, community participation is needed, to contact the fire department so that they can anticipate the fire disaster early. The aim of this research is to develop a forest fire early warning system using the nodemcu module and the Telegram BOT with the Internet of Things (IOT) concept. Based on the test results of the Forest Fire early warning system using the Nodemcu module and the Telegram BOT with the concept of the Internet of Things (IOT) it is very helpful to provide quick information to find out fires that occur in the forest, by using the Internet of Things method, the officer will be able to know the conditions in real time, because this technology is capable of monitoring hardware using internet communication tools such as Telegram so that distance and location are not affected as long as the sensor used detects changes that occur.Keywords: Internet Of Things, Nodemcu, Telegram, Thingspeak, Forest fires